Balloon frontal sinuplasty for intracranial abscess in a pediatric acute sinusitis patient. Issue 3 (March 2015) - Roland, Lauren T.; Wineland, Andre M.; Leonard, David S.
Abstract A case of balloon frontal sinuplasty in a 12-year old male with intracranial abscess from acute sinusitis is presented. The patient experienced photophobia, fever, headache, nausea and vomiting. Frontal sinusitis with intracranial abscess was diagnosed on imaging. The patient was taken to the operating room for drainage with left frontal balloon sinuplasty. The patient showed immediate clinical improvement, did not suffer from any complications of surgery and was further managed with long term intravenous antibiotics. We believe that balloon frontal sinuplasty is potentially safe and effective in the treatment of complicated acute frontal sinus obstruction in children.